Calculus of several variables - Lang, Serge ([S.l.] : Springer, 2012)
This new, revised edition covers all of the basic topics in calculus of several variables, including vectors, curves, functions of several variables, gradient, tangent plane, maxima and minima, potential functions, curve integrals, Green$1 (Bs theorem, multiple integrals, surface integrals, Stokes$1 (Btheorem, and the inverse mapping theorem and its consequences. It includes many completely worked-out probles
Keywords: Functions of several real variables -- Calculus -- Mathematics